CONTRÃ”LE DA LAGARTA â€œELASMOâ€ DO AMENDOIM: Elasmopalpus lignosellus ZELLER, 1918 - Batista, Gilberto Casadei de (REVISTA DE AGRICULTURA, 2015)
CONTRÃ”LE DA LAGARTA â€œELASMOâ€ DO AMENDOIM: Elasmopalpus lignosellus ZELLER, 1918